Mati dan Bangkit Bersama Kristus: Sebuah Spiritualitas Kristen Berdasarkan Refleksi Biblis Kolose 2:16–3:4 - Emanuel Gerrit Singgih; Nindyo Sasongko (Indonesian Journal of Theology, 2017)
What is “spirituality”? The term finds wide usage in the literature today, yet its meaning remains nebulous. One crucial problem lies in how precepts and propositions are maintained as truth, oftentimes becoming obstacles for the flourishing of authentic spirituality. In our reading of Colossians 2:16–3:4, we see the challenges Colossian Christians faced as stemming not from what has been termed the “Colossian heresy,” but rather from what we are calling the “Colossian orthodoxy.” Those who were enthusiastically eager in spiritual matters built stumbling blocks for the spiritual growth of others. In contrast, the epistolary author underscores for the Colossian church just how important is their union with Christ, which must be manifest in their everyday lives. We contend that authentic spirituality relies upon the love of God for the people of God, not on religious precepts.